PENGAWASAN TERHADAP PENANGKARAN SARANG BURUNG WALET DI KOTA PEKANBARU TAHUN 2010-2013 - Rio Mardian Saputra; Erman " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The government expects employers who swallows breeding in order to discipline in accordance with the provisions of yag been set. When employers have an orderly, then the next government's goal is for the preservation of the environment can be maintained. And monitoring can also be done easily. Also, the government can increase revenue Pekanbaru to levy collected. The objective of this policy is every entrepreneur who has conducted or will conduct management activities and procurement of edible bird's nest dihabitat either naturally or outside the natural habitat before or after the enactment of these regulations must obtain a permit from the mayor or his representative with regard spatial Pekanbaru.In this study, the method used is qualitative approach. While data analysis technique that is both descriptive analysis of the spoken word and the observed behavior of the people studied. The research was conducted in the city of Pekanbaru. While the object of his breeding bird nest. Her research focus on monitoring breeding bird nest. The theory used is the control theory H, Bohari SH.Based on the results of research conducted and followed by analyzing the data obtained through interviews, observation, and documentation. After doing some research, the authors conclude that the breeding nest in Pekanbaru city quite well, but in his supervision are still many breeding bird that violates the rules that apply. This is due to the lack of supervision conducted by the department of agriculture and animal husbandry pekanbaru city. From the lack of pengawaan it causes many breeding bird nest that has led to issues such as urban planning pekanbaru were not good and also the negative impact on society is a disease that is arriving at the settlement society due to breeding bird nest.Keywords: Monitoring, Captive Swallow's Nest, Pekanbaru